Perubahan Paon Pada Rumah Tradisional Di Desa Batuan Sukawati - Putu Arya Wiastina Putra; Anak Agung Ayu Sri Ratih Yulianasari (Jurnal Anala, 2020)
Bali is an area famous for its million beauty and charm. The beauty of nature, the hospitality of the people and the sublime Customs and Culture are very valuable assets for Bali in particular and Indonesia in general. Of all the beauty and uniqueness, one thing that is important to note is about Balinese Traditional Architecture which is based on culture and breathes Hinduism. In the study of the construction of Balinese buildings, especially Paon or kitchens, this was carried out to understand more deeply some of the traditional Balinese architectural knowledge that approaches the truth, the direction of development, and the high noble values of our ancestral heritage to be strong and strong. a research was conducted on what changes occurred in the Paon building in the village of Batuan, Sukawati. So that it can be expressed to add to the nation's cultural treasury as a material for information and a comprehensive picture for the Balinese people in particular. The formulation of the problem raised is: How does Paon change in a traditional house in Batuan Village, Sukawati. This study uses an inductive approach to the concept formulated from several elements including: field observations and interviews with experts / experts. It can be concluded: The shape of the Paon building has not changed, but only in terms of materials have changed over time, such as the use of roof covering materials, which all use reeds to become tiles.